2014
DOI: 10.1259/dmfr.20130137
|View full text |Cite
|
Sign up to set email alerts
|

The effect of cone beam CT (CBCT) on therapeutic decision-making in endodontics

Abstract: Objectives: The aim was to assess to what extent cone beam CT (CBCT) used in accordance with current European Commission guidelines in a normal clinical setting has an impact on therapeutic decisions in a population referred for endodontic problems. Methods: The study includes data of consecutively examined patients collected from October 2011 to December 2012. From 2 different endodontic specialist clinics, 57 patients were referred for a CBCT examination using criteria in accordance with current European gui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
55
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(64 citation statements)
references
References 36 publications
4
55
0
5
Order By: Relevance
“…The fourth level included in the current study, therapeutic efficacy, has been presented elsewhere (Mota de Almeida et al . ). The most important objectives of any diagnostic test are to have a positive impact on patient outcome, level 5, and to be cost‐effective, level 6.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The fourth level included in the current study, therapeutic efficacy, has been presented elsewhere (Mota de Almeida et al . ). The most important objectives of any diagnostic test are to have a positive impact on patient outcome, level 5, and to be cost‐effective, level 6.…”
Section: Discussionmentioning
confidence: 97%
“…(), CBCT had no influence on therapy for apical lesions that were easily observed on intra‐oral radiographs but it had the ability to cause endodontic therapy changes when applying the same strict criteria as those applied in the present study (Mota de Almeida et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…The effective radiation dose to patients when using CBCT compared to conventional radiography is much higher, and the benefi t to the patient must be outweighed by any potential risks in order to be justifi ed. Radiation dose should be kept as low as reasonably achievable (ALARA) [ 6 ]. Conventional two-dimensional (2D) radiographs provide a cost-effective, high-resolution image, which continues to be the most popular method of imaging today [ 6 ].…”
Section: Overview Of Radiology and Endodonticsmentioning
confidence: 99%
“…Radiation dose should be kept as low as reasonably achievable (ALARA) [ 6 ]. Conventional two-dimensional (2D) radiographs provide a cost-effective, high-resolution image, which continues to be the most popular method of imaging today [ 6 ]. According to the consensus report of the European Society of Endodontology, appropriate root canal treatment includes a radiographical control showing a prepared root canal tapered from crown to apex and fi lled completely without space between canal fi lling and canal walls [ 7 ].…”
Section: Overview Of Radiology and Endodonticsmentioning
confidence: 99%
“…The usefulness of CBCT for therapeutic decision-making in endodontics was indicated by Mota de Almeida et al 4 , whereby differences in endodontic treatment planning were compared before and after CBCT examination. The results showed that over half of the changes in treatment planning were attributed to CBCT ndings.…”
mentioning
confidence: 99%